The Last War: A Screenplay Depicting Optimism In A Post-Apocalyptic World - Michael Wenardi Gunawan; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
Optimism is an important thing for many people in order to maintain world peace. More specifically, optimism can still play a major role even when the world is in a post-apocalyptic state. Therefore, this creative work has been made to show how optimism can make a big difference in the post-apocalyptic era. The creative work will use the theory of optimism by Martin Seligman in his book ‘Learned Optimism’. The creative work will be in the post-apocalyptic genre, and will use the screenplay film format. The result of the making of the creative work is people will be more knowledgeable about optimism through the actions of the protagonist. In addition, more people will know about the effects of optimism through the character development of the protagonist and the ways it can make the world better at the conclusion of the creative work.